Revisiting Myths Associated With Derivatives: An Empirical Study - Sandhu, Namrata; Sandhu, Sahil Singh (Indian Journal of Finance, 2012)
Literature on financial derivatives is replete with myths associated with them. The current study attempts to examine whether they are still prevalent amongst investors in India even though over a decade has passed since organized trading in financial derivatives was first introduced in India. After an empirical analysis of the views of 177 investors, it was revealed that myths about derivatives are rampant among the investors who believe them to be very complex, high-risk instruments unsuitable for Indian markets. They also lack faith in the regulatory mechanism surrounding derivatives trading. These misconceptions need to be effectively dispelled before derivatives can be invested in and understood in the spirit in which they were originally designed. This will also contribute towards improving the volume of derivatives trading in India.